Dietary oxidized beef protein alters gut microbiota and induces colonic inflammatory damage in C57BL/6 mice - Yin, Yantao; Cai, Jiaming; Zhou, Lei; Xing, Lujuan; Zhang, Wangang (Frontiers in Nutrition, 2022)
This study aimed to investigate the effect of oxidized beef protein on colon health. C57BL/6 mice were fed diets containing in vitro oxidized beef protein or normal beef protein (control group) for 10 weeks. Histological observations showed that oxidized beef protein diet induced notable inflammatory cell infiltrations in colon. The analysis of high-throughput sequencing indicated oxidized beef protein largely altered the composition of gut microbiota (GM) by increasing proinflammatory bacteria (Desulfovibrio, Bacteroides, Enterorhabdus) while reducing beneficial bacteria (Lactobacillus, Akkermansia). In addition, oxidized beef protein remarkably increased protein fermentation in the colon, which was evidenced by the elevated i-butyrate, i-valerate, and ammonia levels in feces. Furthermore, consuming oxidized beef protein destroyed colon barrier functions by decreasing tight junction proteins expression. These changes in colonic ecosystem activated the proinflammatory pathway of lipopolysaccharide/toll-like receptor-4/nuclear factor kappa B (LPS/TLR-4/NF-κB), eventually leading to colonic inflammatory damage in mice. Taken together, these results imply that consuming oxidized beef protein detrimentally regulates GM and impairs colon health.